2017
DOI: 10.3390/nu9050450
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Efficiency of the Reticulocyte Hemoglobin Content on Diagnosis for Iron Deficiency Anemia in Chinese Adults

Abstract: Our aim was to evaluate the cut-off value and efficiency of using reticulocyte hemoglobin content as a marker to diagnose iron deficiency anemia in Chinese adults. 140 adults who needed bone marrow aspiration for diagnosis at the hematology department of the Peking Union Medical College Hospital were enrolled according to the inclusive and exclusive criteria. Venous blood samples were collected to detect complete blood count, including hemoglobin, reticulocyte hemoglobin content, hematocrit, mean cellular volu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
1
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 23 publications
2
26
1
4
Order By: Relevance
“…Peripheral blood test is commonly used in clinical practice. Blood routine test (BRT), as one of the most basic peripheral blood biochemical tests, can quickly and accurately detect the values of blood components such as white blood cells (WBC), lymphocytes (LY), red blood cells (RBC), hemoglobin (HGB) and platelets (PLT), as well as other related indicators, in order to effectively indicate abnormalities of infection, anemia and cruor [7][8][9] . In recent years, a wide variety of blood indicators with different changes were concerned and discussed in the study of malignant tumor diseases including CRC: Qian W, et al reported that the post-/pre-treatment MPV (Mean Platelet Volume) ratio were prognostic factors for OS in resectable CRCs [10] ; Preoperative neutrophil-lymphocyte ratio (NLR) and red blood cell distribution width (RDW), especially the independent prediction of NLR, were confirmed as effective biomarkers for clinical diagnosis and prognosis evaluation of esophageal cancers [11] ; In patients with pathologic stage I non-small cell lung cancer undergoing surgical resection, high LY and PLT count from peripheral blood could provide poor prognostic value independently [12] ; Even the ratios between indicators were developed into new indexes, which had fairly good prognostic significance, including NLR, Platelet-to-Lymphocyte Ratio (PLR), Lymphocyte-to-Monocyte ratio (LMR).…”
Section: Ivyspringmentioning
confidence: 99%
“…Peripheral blood test is commonly used in clinical practice. Blood routine test (BRT), as one of the most basic peripheral blood biochemical tests, can quickly and accurately detect the values of blood components such as white blood cells (WBC), lymphocytes (LY), red blood cells (RBC), hemoglobin (HGB) and platelets (PLT), as well as other related indicators, in order to effectively indicate abnormalities of infection, anemia and cruor [7][8][9] . In recent years, a wide variety of blood indicators with different changes were concerned and discussed in the study of malignant tumor diseases including CRC: Qian W, et al reported that the post-/pre-treatment MPV (Mean Platelet Volume) ratio were prognostic factors for OS in resectable CRCs [10] ; Preoperative neutrophil-lymphocyte ratio (NLR) and red blood cell distribution width (RDW), especially the independent prediction of NLR, were confirmed as effective biomarkers for clinical diagnosis and prognosis evaluation of esophageal cancers [11] ; In patients with pathologic stage I non-small cell lung cancer undergoing surgical resection, high LY and PLT count from peripheral blood could provide poor prognostic value independently [12] ; Even the ratios between indicators were developed into new indexes, which had fairly good prognostic significance, including NLR, Platelet-to-Lymphocyte Ratio (PLR), Lymphocyte-to-Monocyte ratio (LMR).…”
Section: Ivyspringmentioning
confidence: 99%
“…7,8 They also found that CHr has a high sensitivity and specificity in the diagnosis of IDA, and its comprehensive diagnostic efficacy is better than other traditional indicators such as Transferrin Saturation and sTfR. 9 CHr is much more cost efficient compared to doing current diagnostic panel; as it can be obtained as part of the complete blood count in most of the modern-day analysers, at no extra cost or additional blood sample. CHr can also be used to evaluate response to Iron therapy at the earliest in comparison to other hematological parameters.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, new indices of red blood cells have emerged in parallel with technological developments, including both erythrocytes and maturing cells (i.e., reticulocytes). These new parameters, measured simultaneously with basic blood morphology, are helpful in assessing iron status in healthy subjects [10,11,12,13,14,15] and patients with various disorders [2,16,17]. Due to the short life span of reticulocytes (i.e., 24–48 h), markers of maturing red blood cells offer some diagnostic value in assessing subclinical ID [2,18,19].…”
Section: Introductionmentioning
confidence: 99%